Parameter identification of nonlinear time-dependent rubber bushings models towards their integration in multibody simulations of a vehicle chassis - Puel, Guillaume; Bourgeteau, Béatrice; Aubry, Denis (Mechanical systems and signal processing, 2013)
Rubber bushings are extensively used linking parts in a vehicle chassis that allow to filter noise and vibration. They influence much, however, the transient behavior of the vehicle, such as its steering performance. Therefore, building a multibody simulation with a relevant description of the rubber bushings is useful to describe the significant characteristics of the vehicle's steering behavior. First, a nonlinear time-dependent model describing a rubber bushing's mechanical behavior is presented. In order to be relevant, the parameters associated with this model are then identified from experimental tests using an adjoint state formulation of the identification problem. The identified values are eventually validated using additional experimental data. ► A simple but relevant mechanical model for rubber bushings is proposed. ► This model can be easily implemented in a multibody simulation software. ► The parameters are identified with a time gradient-based minimization algorithm. ► Smoothing of the model's discontinuities is required to get correct results. ► The method can be applied to any transient problem with contact-type phenomena.